Evolution of parasitism: kinetoplastid protozoan history reconstructed from mitochondrial rRNA gene sequences. - Lake, J A (1988)
A phylogenetic tree for the evolution of five representative species from four genera of kinetoplastid protozoa was constructed from comparison of the mitochondrial 9S and 12S rRNA gene sequences and application of both parsimony and evolutionary parsimony algorithms. In the rooted version of the tree, the monogenetic species Crithidia fasciculata is the most deeply rooted, followed by another monogenetic species, Leptomonas sp. The three digenetic species Trypanosoma cruzi, Trypanosoma brucei, and Leishmania tarentolae branch from the Leptomonas line. The substitution rates for the T. brucei and T. cruzi sequences were 3-4 times greater than that of the L. tarentolae sequences. This phylogenetic tree is consistent with our cladistic analysis of the biological evidence including life cycles for these five species. A tentative time scale can be assigned to the nodes of this tree by assuming that the common ancestor of the digenetic parasites predated the separation of South America and Africa and postdated the first fossil appearance of its host (inferred by parsimony analysis). This time scale predicts that the deepest node occurred at 264 +/- 51 million years ago, at a time commensurate with the fossil origins of the Hemiptera insect host. This implies that the ancestral kinetoplastid and its insect host appeared at approximately the same time. The molecular data suggest that these eukaryotic parasites have an evolutionary history that extends back to the origin of their insect host.